(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2018)
This research falls within the area of developmental psychology, particularly with regard to the promotion of the child’s psychological development considering the educational context. It was specifically intended to study the importance to the psychological development of children of its sojourn at early ages in daycare educational contexts, basing the pedagogical intervention in a proposed program, based on the High/Scope curricular approach (Post and Hohmann, 2011), as well as on the Portage model (Williams y Aiello, 2009). Assuming as a primary objective the promotion of the psychological development of these children, it becomes a pressing need to reflect on educational interventions for early ages, being also of significant importance that these are properly supported in scientific theories of human development. We advocated, then, to develop a researchaction with a quasi-experimental component, whose results would allow to envisage a curriculum for the context of childcare, which could activate the psychological development of children and qualitatively raise the educational intervention. Thus, in this study, with the participation of children (N = 59) aged about two years old, and also with their kindergarten teachers (N = 4), it was intended, through a comparative study between groups of children, subjected or not to the above mentioned program and under this research, to know its impact on the psychological development using, in the pre and post-test phases, observation/appreciation grids of this development for children in childcare age. With particular regard to the data collected is possible to advance that children who were part of the experimental groups, which were subject to an intervention program, showed higher gains in the post-test phase at the level of development of motor skills, language, cognitive development and affective and relational development, comparing to the children of the control groups, who experienced a natural educational intervention. Implications are presented.